High-performance microfluidic rectifier based on sudden expansion channel with embedded block structure - Tsai, Chien-Hsiung (American Institute of Physics, 2012)
A high-performance microfluidic rectifier incorporating a microchannel and a sudden expansion channel is proposed. In the proposed device, a block structure embedded within the expansion channel is used to induce two vortex structures at the end of the microchannel under reverse flow conditions. The vortices reduce the hydraulic diameter of the microchannel and, therefore, increase the flow resistance. The rectification performance of the proposed device is evaluated by both experimentally and numerically. The experimental and numerical values of the rectification performance index (i.e., the diodicity, Di) are found to be 1.54 and 1.76, respectively. Significantly, flow rectification is achieved without the need for moving parts. Thus, the proposed device is ideally suited to the high pressure environment characteristic of most micro-electro-mechanical-systems (MEMS)-based devices. Moreover, the rectification performance of the proposed device is superior to that of existing valveless rectifiers based on Tesla valves, simple nozzle/diffuser structures, or cascaded nozzle/diffuser structures.